Factor analysis as a method of classifying organizations-bank borrowers (Путеводитель предпринимателя, 2020)
The purpose of the study is to obtain the classification of organizations-borrowers by financial and economic indicators on basis of factor analysis as a method of multivariate mathematical statistics.